Bangladeshi Wild Date Palm Fruits (Phoenix sylvestris): Promising Source of Anti-cancer Agents for Hepatocellular Carcinoma Treatment - Lamia, Farhana Shikder; Mukti, Roushney Fatima (International Journal of Applied Sciences and Biotechnology, 2021)
Many natural products such as fruits and vegetables are promising amends as safe, effective and affordable approaches to control cancer development and progression, since they are inexpensive and available without any hazards. For instance, the aqueous extract of Ajwa dates (Phoenix dactilyfera) has been found to improve liver function through the restoration of anti-oxidant enzymes, liver enzymes, and cytokines balance and gene expression to normal levels. As the treatment and prognosis of Hepatocellular carcinoma, one of the leading causes of cancer associated deaths globally, has been found to be better if the liver function of the patient can be preserved, Ajwa date extract has been used together with the conventional therapeutics for the treatment of this disease. However, no study has been conducted so far on the anticancer activity of Bangladeshi wild date palm fruits (Phoenix sylvestris) despite the fact that it contains apigenin, quercetin, glucans, luteolin, and iron and vitamin complex. Therefore, in this review we discussed an idea that potential anticancer agents can be isolated from the extract of these fruits, which can eventually be used as an indigenous substance for the treatment of Hepatocellular carcinoma in our country and also the liver cancer inhibitory effects of the aqueous extract of these dates can be evaluated in rat model. Int. J. Appl. Sci. Biotechnol. Vol 9(1): 32-37